Immune regulation during chronic visceral leishmaniasis. - Rebecca J Faleiro; Rajiv Kumar; Louise M Hafner; Christian R Engwerda (Public Library of Science (PLoS), 2014)
Visceral leishmaniasis is a chronic parasitic disease associated with severe immune dysfunction. Treatment options are limited to relatively toxic drugs, and there is no vaccine for humans available. Hence, there is an urgent need to better understand immune responses following infection with Leishmania species by studying animal models of disease and clinical samples from patients. Here, we review recent discoveries in these areas and highlight shortcomings in our knowledge that need to be addressed if better treatment options are to be developed and effective vaccines designed.